UNDERSTANDING OF NON-VALUE ADDED OVERTIME IN MANUFACTURING OPERATIONS - A. H. ABDUL RASIB , M. MUSAZALI (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
: The manufacturing industry plays a crucial role in the production process to meet the demands of the market and to raise the standard of living recently. Nevertheless, one of the most common issues associated with the industry is unnecessary overtime. Overtime has produced a variety of negative consequences on production output. This paper aims to identify the various causes of unnecessary overtime, and the causes have been categorised through the seven wastes of lean manufacturing. This paper also focuses on unnecessary overtime occurred in industries. The method used in this paper is by reviewing the relevant literature from conference papers and journal publications, including the International Journal of Scientific and Technology Research, Journal of Advanced Manufacturing Technology, and International Journal of Engineering and Technology, amongst many others. Finally, the critical components of NAO have been finalised according to the necessaryscopes of operation,which considered as factors which are pre-production, in-production, and postproduction.Based on the final critical components, there were two critical sub-factors in preproduction components, six critical sub-factors in-production elements, and five critical subfactors post-production components.